Effectiveness of Large-Scale Marine Protected Areas in the Atlantic Ocean for Reducing Fishing Activities - Magris, Rafael Almeida (Frontiers in Marine Science, 2021)
The implementation of large-scale marine protected areas (MPAs) depends upon scarce conservation resources, while their effects on biodiversity conservation are rarely assessed to date. Quantitative evaluations are necessary to assess the effectiveness of large-scale MPAs in enhancing ecosystem resilience, protecting biodiversity, and mitigating expanding threats. In this study, the effectiveness of large-scale MPAs, which are remotely managed and in offshore areas of the southwestern Atlantic Ocean (Brazil), was assessed concerning the occurrence of fishing activities within their boundaries before and after their implementation. Two sets of MPAs surrounding the São Pedro and São Paulo archipelago (SPSP) and the Trindade-Martin Vaz Islands (TMV) were established in early 2018, each comprising one no-take (i.e., fully-protected) and one multiple-use (i.e., partially-protected) area. For this assessment, I used satellite detections of Vessel Monitoring System transmission to quantify the fishing pressure (i.e., “likely fishing days”) from commercial fisheries spanning 5 years (2015–2019). I then derived three metrics – fishing area, intensity, and density – to compare fishing activity within each MPA and year. The results showed that the effectiveness of the multiple-use MPAs was variable and contrasting, with SPSP experiencing a reduction in the fishing intensity and area and TMV experiencing an increase in both measures. An inverted pattern was evident for the no-take MPAs: while the one in the SPSP region experienced an increase in the fishing density after its establishment following a squeeze factor, the no-take MPA in the TMV region observed a decrease in the fishing density when comparing years before and after MPA implementation. These outputs can support managers in planning the implementation of further conservation strategies, such as monitoring and enforcement plans, and the analyses here also contribute to enhancing our understanding on the implications and challenges of adopting large-scale MPAs in the offshore environment as a high-profile strategy of ocean conservation.